INTERDICTION ACTIONS AGAINST THE ILEGAL FISHING - Da Fieno Jibaja, Daniel (2019)
The recently approved Legislative Decree that regulates interdiction actions in illegal fishing activities represents a step forward in strengthening the fight against this threat that harms the sustainable use of hydrobiological resources. Although there is still a lot of work to be done, it is a success and demonstrates a real commitment and interest on the part of the State to return our fishery to its rightful place. End informality, which affects most of the productive activities of our country, in a sector so crucial for national development is not an easy task; However, this effort is added to the already developed tasks that, under the baton of the General Directorate of Captaincies and the Ministry of Production, have been carried out throughout our 200 nautical miles.